God's property: Islam, charity, and the modern state - Moumtaz, Nada (Islamic humanities, 2021)
Waqf, a non-definition -- State, law, and the "Muslim community" -- The intent of charity -- Charity and the family -- The "Waqf's benefit" and public benefit -- Conclusion -- Appendix A. Main Ottoman Mutūn and their main commentaries and glosses -- Appendix B. Umari mosque expenditures and appointments.